Women Endure COVID-19 Unequally to Men - World Bank (World Bank, Washington, DC, 2020)
The adverse impact of the Coronavirus (COVID-19) pandemic is being disproportionately borne by women, further exacerbating the wide gender inequities in Myanmar. From food security, shortages in finances and the burden of caretaking responsibilities, women have been disproportionately affected by the secondary impacts of the Coronavirus (COVID-19) outbreak. Women have had to adopt more drastic measures to mitigate the impacts of the pandemic, both reactively and proactively, ranging from reducing food- and non-food consumption and borrowing money from Micro-Finance Institutions and informal money lenders. Not unexpectedly, women’s greater disadvantage, limited access to support, subjection to domestic violence and structural inequalities lend themselves to their being less optimistic about the near future. The evidence surveyed is clear that women are enduring Coronavirus (COVID-19) disproportionately worse than men, both in household and firm settings and they take on the bulk of the emotional burden with regard to responsive and proactive coping mechanisms.